TUBUH PEREMPUAN DALAM BUDAYA KONSUMEN: ANTARA KESENANGAN DIRI, STATUS SOSIAL, DAN NILAI PATRIARKI - ida Rosida (Universitas Andalas, 2018)
This article discusses the Jakarta urban women body in Indonesian consumer culture as reflected in Miss Jinjing Belanja Sampai Mati (2008) by Amelia Masniari. Within consumer culture, consuming commodities is seen as a natural. However, it is the impact of the power (dominant ideologies) that present in that culture. The primary objective of this paper is to explore how the Jakarta urban woman body is constructed within Indonesia’s consumer culture in which portrayed in Miss Jinjing Belanja Sampai Mati (2008) through the character of Amelia Masniari. This is a qualitative research with cultural studies approach. The concept of Mike Featherstone about the body in consumer culture is used to analyze the text. The results show that the Jakarta urban woman body as reflected through Amelia's character is constructed by capitalism, consumerism and patriarchal ideology. The emergence of these three ideologies are seen through contradictions in the text such as the contradiction between values of self-pleasure, social status as well as patriarchal values. In conclusion, the Jakarta urban woman body (Amelia) in Indonesian consumer culture as reflected in Miss Jinjing Belanja Sampai Mati (2008) is site of ideological contestation; capitalism, consumerism and patriarchal ideology. The presence of these ideologies are not mutually tearing down but mutually reinforcing one another and in the end there is coherence between each ideology.